Psychometric study of bar-on emotional quotient inventory: Youth version in Malaysian sample - Chua Bee Seok; Shazia Iqbal Hashmi; Lailawati Madlan; Jasmine Adela Mutang (Universiti Putra Malaysia, 2020)
The concept of emotional intelligence (EQ) is an important topic among today’s modern society. People are now gaining realisation that these skills can help them in better managing both their professional and personal lives. However, scales available to measure EQ are limited especially among the Malaysian population. Therefore, this study sought to investigate the psychometric proprieties of the Bar-On Emotional Youth Version Quotient Inventory (EQi:YV) in Malaysian samples. A total of 728 students aged between 14 to 20 years old from four secondary schools in Kota Kinabalu, Sabah participated in this study. The EQ-i:YV contains 35 self-report items designed to assess: Intrapersonal, Interpersonal, Adaptability, and Stress Management. The Structural Equation Modelling was used to assess the suitability of the model. The reliability and validity of the model were also measured. Confirmatory factor analysis was employed to test its compatibility. Multiple goodness-of-fit indicators initially revealed that the measurement model failed to reach some of the recommended standards for model fitness. After necessary adjustments were made, the modified model, which retained 30 items, produced a better level of fitness and met recommended standards. The analysis found that EQi: YV had a satisfactory level of reliability despite some convergent and discriminant validity issues. Overall, the EQi:YV is suitable for use in the Malaysian context. Recommendations for future research are also discussed.